Extreme floods increase CO2 outgassing from a large Amazonian river. (15th February 2017) - Almeida, Rafael M.; Pacheco, Felipe S.; Barros, Nathan; Rosi, Emma; Roland, Fábio
Abstract: Large Amazonian rivers are characteristically subject to seasonal floods. We examine how inundation extent affects the partial pressure of carbon dioxide (pCO2 ) and CO2 outgassing in the Madeira River, a large tributary to the Amazon River. We show data from nine field campaigns performed between 2009 and 2011, complemented with data from one additional campaign in April 2014 that is representative of the largest flood on record. Both the pCO2 (range, 835–9694 μ atm) and CO2 outgassing (range, 641–12, 253 mg C m −2 d −1 ) had large seasonal variability (with peaks during high water), and fit exponential relationships with water level. CO2 outgassing per unit area in 2014 was 50% higher than the other highest rate in our dataset. Reconstruction of CO2 fluxes since 1968 indicates that extreme‐flood years outgas 20% more CO2 per unit area than years without reported occurrence of extreme floods. Our findings indicate a positive feedback between climate change, extreme flooding, and CO2 outgassing from river water.